PENDAMPINGAN PENGOLAHAN IKAN BANDENG (Chanos chanos) TANPA DURI PADA KELOMPOK WANITA DI KELURAHAN TALISE KOTA PALU - Raheni, Cahyaning; Putra, Setiawan Mandala; Umar, Umar; Hak, Nasrul; Mutmainah, Mutmainah; Mande, Henni; Burhanuddin, Burhanuddin; Kasih, Ulfa Cahyaning (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2024)
The aim of this community service activity is to increase family income through processing milkfish. The target of this Community Service activity is the Women's group which is carried out in Talise Subdistrict, Palu City, Central Sulawesi. The methods of implementing the activities are presentation of material, training (practice), mentoring, and evaluation. As a result of implementing this activity, it is hoped that the community, especially the women's group in Talise Subdistrict, will have understanding and knowledge in processing and producing milkfish into healthy culinary delights and will be able to produce processed milkfish to increase the income of the people of Talise Subdistrict, especially women's groups.